1994
DOI: 10.1001/archpsyc.1994.03950110009002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Interview for Genetic Studies

Abstract: This article reports on the development and reliability of the Diagnostic Interview for Genetic Studies (DIGS), a clinical interview especially constructed for the assessment of major mood and psychotic disorders and their spectrum conditions. The DIGS, which was developed and piloted as a collaborative effort of investigators from sites in the National Institute of Mental Health (NIMH) Genetics Initiative, has the following additional features: (1) polydiagnostic capacity; (2) a detailed assessment of the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
481
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,880 publications
(485 citation statements)
references
References 47 publications
2
481
0
2
Order By: Relevance
“…The relationship between depression and hippocampal size, however, is controversial. While some MRI studies (Nurnberger et al 1994;Sheline et al 1996) reported significantly reduced hippocampal volumes in major depression, other studies found no reduction (Axelson et al 1993b;Vakili et al 2000), although depression severity and treatment response correlated with hippocampal size (Vakili et al 2000). In conclusion, there remain questions concerning the role of potential confounding variables in the previously reported MRI data in PTSD.…”
Section: Discussionmentioning
confidence: 90%
“…The relationship between depression and hippocampal size, however, is controversial. While some MRI studies (Nurnberger et al 1994;Sheline et al 1996) reported significantly reduced hippocampal volumes in major depression, other studies found no reduction (Axelson et al 1993b;Vakili et al 2000), although depression severity and treatment response correlated with hippocampal size (Vakili et al 2000). In conclusion, there remain questions concerning the role of potential confounding variables in the previously reported MRI data in PTSD.…”
Section: Discussionmentioning
confidence: 90%
“…For the at‐risk cohort, proband consensus DSM‐IV diagnoses were determined by two independent psychiatrists using best estimate methodology [Leckman et al, 1982], using information from an adapted version of the Schedule for Affective Disorders and Schizophrenia for School‐Age Children—Present and Lifetime Version (K‐SADS‐BP) [Kaufman et al, 1997; Geller et al, 2001], the Diagnostic Interview for Genetic Studies (DIGS) Version 4 [Nurnberger et al, 1994], the Family Interview for Genetic Studies (FIGS) [Maxwell, 1992], and medical records (where available). For participants under the age of 22, the K‐SADS‐BP was administered as the diagnostic instrument.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there is a lower threshold for NMDA receptor antagonist mediated neurotoxicity in female rats (Olney et al 1989) and this study sought a maximum safety margin (see Ketamine Dosing and Safety Considerations below). Sub-jects were interviewed using the Diagnostic Instrument for Genetic Studies (Nurnberger et al 1994). A senior clinician reviewed all data to determine whether subjects met criteria for any DSM-IV diagnoses.…”
Section: Subjectsmentioning
confidence: 99%
“…A senior clinician reviewed all data to determine whether subjects met criteria for any DSM-IV diagnoses. Subjects were also interviewed with the Family Instrument for Genetic Studies (Nurnberger et al 1994) in order to identify relevant psychopathology within first degree relatives; none was detected in this sample.…”
Section: Subjectsmentioning
confidence: 99%